Catalytic activity of trypsin entrapped in electrospun poly(e-caprolactone) nanofibers - Pinto, Susana C.
Trypsin was successfully entrapped in situ into nanofibers of poly(e-caprolactone) (PCL) prepared byelectrospinning. The spinning dope was an emulsion consisting of an aqueous phase with the solubilizedenzyme in a pH buffer plus an oil phase of the polymer solubilized in chloroform (CF)/dimethylformamide(DMF). The optimized materials were composed by random arrays of bead-free fibers with outer diam-eters in the range 110–180 nm without showing core–shell structure. The fiber size and morphology,membrane porosity and surface properties were shown to be influenced by the polymer concentration and the composition ratio of the solvent mixture, and also by the presence of the enzyme. The activity ofthe immobilized trypsin was studied toward both a low-molecular weight synthetic substrate (BAPNA) and a protein (casein). Fluorescence microscopy, the increasing hydrophilicity of the fibrous membrane and the observed catalytic activity confirmed the entrapment of the enzyme into the PCL nanofibers.The best activity retention (∼66% toward BAPNA) was achieved using 0.20 g/mL PCL in CF/DMF [75:25],with trypsin in an aqueous buffer at pH 7.1 in the presence of benzamidine and Span80. The immo-bilized enzyme showed satisfactory operational stability retaining ∼59% of its initial activity after five reaction cycles. Compared with the free enzyme, the storage (at 4◦C) and thermal stability of the immobilized enzyme were highly improved. The retained catalytic activity and the observed reusability can beexplained by a heterogeneous distribution of the enzyme within the polymer fiber influenced by the electrostatic field during the electrospinning process, enabling a preferential location near the fiber surfacebut simultaneously assuring minimal leaching out during operations. Results suggest that trypsin-PCLfibrous membranes may be useful for concomitant proteolytic and separation commercial applications.